A magneto-active soft gripper with adaptive and controllable motion. (9th December 2020) - Li, Xianghao; Zhang, Zheng; Sun, Min; Wu, Helong; Zhou, Yisong; Wu, Huaping; Jiang, Shaofei
Abstract: Bionic soft grippers that can gently conform to the objects of any profiles and softly hold them with uniform pressure have been receiving considerable attention. To realize rapid and non-contact driving, a novel magneto-active soft gripper is developed in this paper. The gripper is embedded with magneto-active elastomer (MAE) actuators that are made from a mixture of a soft material substrate and hard magnetic fillers. Firstly, the MAE actuators doped with different contents of magnetic fillers are manufactured and magnetized by applying an external magnetic field. An experiment is designed to measure the magnetically induced deformation of MAE actuators under different external magnetic fields. On basis of the experimental study of MAE actuators, the magneto-active soft gripper is then designed and successfully fabricated. The gripping function and efficiency of the magneto-active soft gripper is demonstrated through an experimental study. Meanwhile, the maximum gripping force of grippers is measured and the effects of applied magnetic field and mass faction of magnetic fillers are examined. It is found that the gripping force increases as either magnetic field strength or magnetic fillers' concentration increases but tends to be stable when the magnetic field is greater than 80 mT. When executing a gripping motion, the magneto-active soft gripper has a significantly short response time than the existing ones with other driving methods.